Phase transitions in confinements: controlling solid to fluid transitions of xenon atoms in an on-surface network - Ahsan, Aisha; Gade, Lutz H. (Small, 2019)
This study reports on “phase” transitions of Xe condensates in on-surface confinements induced by temperature changes and local probe excitation. The pores of a metal-organic network occupied with 1 up to 9 Xe atoms are investigated in their propensity to undergo “condensed solid” to “confined fluid” transitions. Different transition temperatures are identified, which depend on the number of Xe atoms in the condensate and relate to the stability of the Xe clustering in the condensed “phase.” This work reveals the feature-rich behavior of transitions of confined planar condensates, which provide a showcase toward future “phase-transition” storage media patterned by self-assembly. This work is also of fundamental interest as it paves the way to real space investigations of reversible solid to fluid transitions of magic cluster condensates in an array of extremely well-defined quantum confinements.